2022
DOI: 10.1093/plphys/kiac237
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-like protein kinase BAK1 promotes K+ uptake by regulating H+-ATPase AHA2 under low potassium stress

Abstract: Potassium (K+) is one of the essential macronutrients for plant growth and development. However, the available K+ concentration in soil is relatively low. Plant roots can perceive low K+ (LK) stress, then enhance high-affinity K+ uptake by activating H+-ATPases in root cells, but the mechanisms are still unclear. Here, we identified the receptor-like protein kinase BAK1 (Brassinosteroid Insensitive 1-Associated Receptor Kinase 1) that is involved in LK response by regulating the Arabidopsis (Arabidopsis thalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…In this study, we discovered that Thr-881 is also phosphorylated in guard cells in both blue light- and photosynthesis-dependent manners. A recent study suggested that Thr-881 is phosphorylated in plants in response to low K + treatments 36 . Thus, the phosphorylation level of Thr-881 appears to be regulated as a terminal point in the signalling pathways of various external cues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we discovered that Thr-881 is also phosphorylated in guard cells in both blue light- and photosynthesis-dependent manners. A recent study suggested that Thr-881 is phosphorylated in plants in response to low K + treatments 36 . Thus, the phosphorylation level of Thr-881 appears to be regulated as a terminal point in the signalling pathways of various external cues.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effect of the C-terminal domain on H + -ATPase activity is thought to be caused by two regions (regions I and II) which possibly interact and interfere with the catalytic domains 32 , 35 . The Thr-881 of AHA1 in region I is highly conserved in plants, and a recent study showed that AHA2 phosphorylation at Thr-881 is enhanced in Arabidopsis roots under low K + conditions 36 . Mutational experiments using a yeast heterologous expression system have indicated that the phosphorylation of Thr-881 increases H + -ATPase activity without affecting 14-3-3 protein binding 37 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have assessed protein phosphorylation modifications of PM H + ‐ATPase. Multiple kinases, such as PSYR1, BAK1 and CDK1, phosphatases PP2A/2C, can regulate PM H + ‐ATPase activity by phosphorylating or dephosphorylating PM H + ‐ ATPase (Fuglsang et al., 2006; Pei et al., 2022; Wang et al., 2022). MAPK cascade is a highly conserved and classical kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Several phospho‐sites of AHA2, such as Thr881, Ser899, Ser944, Thr947 and other sites have been identified in Arabidopsis (Fuglsang & Palmgren, 2021; Pei et al., 2022; Wang et al., 2022). Different phosphorylation sites have different effects on the activity of PM H + ‐ATPase.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of net K + uptake rate followed previously described procedures with some modifications (Wang et al ., 2022). The seedlings at the three‐leaf stage under CK or LK with equal fresh weight were taken out of the solutions and transferred to a K + ‐free solution (200 μM CaSO 4 , 5 mM MES, pH 5.7 adjusted with Tris) for 48 h. They were subsequently put into a fresh K + depletion solution (80 μM KNO 3 , 200 μM CaSO 4 , 5 mM MES, pH 5.7 adjusted with Tris).…”
Section: Methodsmentioning
confidence: 99%